Band Energy Outline of NiO:Au /Si Thin-Film for Solar Cell - Jamal, Raied K. (Iraqi Journal of Science, 2021)
In this paper the effects of the contact material on the photovoltaic (PV) characteristics of p-NiO:Au/n-Si solar cells fabricated by using the pulsed laser deposition (PLD) technique had been studied. It shown the p-NiO:Au/n-Si could be successfully used to construct and improve the performance of solar cells by using Au. The conversion efficiency was increased comparable with p-NiO/n-Si solar cells. In this case the NiO:Au layer acts as a hole collector as well as a barrier for charge recombination.